SOCIO-PSYCHOLOGICAL CHARACTERISTICS OF A MODERN TEACHER IN THE DIGITAL AGE - Petrash, Elena; Sidorova, Tatyana; Blum, Vera; Zaia, Iosif; Manuilova, Ekaterina (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
The article focuses on a teacher undergoing a transformation in the digital age. The authors considered the main socio-psychological characteristics of a modern teacher, conducted an empirical research and supplemented the professionogram of a modern teacher. The program of teachers’ professional development proposed by the authors is based on the idea of system-activity and anthropological approaches.